2010
DOI: 10.1080/87565641.2010.508549
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linguistic Auditory Processing and Working Memory Update in Pre-School Children Who Stutter: An Electrophysiological Study

Abstract: Non-linguistic auditory processing and working memory update were examined with event-related potentials (ERPs) in 18 children who stutter (CWS) and 18 children who do not stutter (CWNS). Children heard frequent 1kHz tones interspersed with rare 2kHz tones. The two groups did not differ on any measure of the P1 and N1 components, strongly suggesting that early auditory processing of pure tones is unimpaired in CWS. However, as a group, only CWNS exhibited a P3 component to rare tones suggesting that developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
46
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 79 publications
(104 reference statements)
7
46
1
5
Order By: Relevance
“…To the best of our knowledge, only a few studies have examined the neural correlates of stuttering in children (Beal et al, 2011;Beal, 2010;Chang et al, 2008;Kaganovich et al, 2010;Sato et al, 2011;Weber-Fox, Spruill, Spencer, & Smith, 2008;Weber-Fox, Hampton Wray, & Arnold, 2013). Neuroanatomical studies conducted by Chang et al (2008) and Beal (2010) showed reduced gray matter volume in children who stutter (CWS) in the left inferior frontal gyrus, and in temporal regions, compared to typically developing children with fluent speech.…”
mentioning
confidence: 99%
“…To the best of our knowledge, only a few studies have examined the neural correlates of stuttering in children (Beal et al, 2011;Beal, 2010;Chang et al, 2008;Kaganovich et al, 2010;Sato et al, 2011;Weber-Fox, Spruill, Spencer, & Smith, 2008;Weber-Fox, Hampton Wray, & Arnold, 2013). Neuroanatomical studies conducted by Chang et al (2008) and Beal (2010) showed reduced gray matter volume in children who stutter (CWS) in the left inferior frontal gyrus, and in temporal regions, compared to typically developing children with fluent speech.…”
mentioning
confidence: 99%
“…The participants' ages ranged from 2 months (23) to 12 years of age (4,12,19,22,35,37) . Regarding the parameters used to perform the MMN, most of the research used the speech stimulus (4,(20)(21)(22)(23)(24)(25)(26)30,(32)(33)(34)(35)(36) and other studies opted to perform the MMN with tone burst stimulus (12,19,22,(27)(28)(29)31,(37)(38)(39) . Regarding the tone burst stimulus, it was verified that some studies evaluated with frequency variation (12,(27)(28)(29)31,(37)(38)(39) and 1, by duration and frequency (19) .…”
Section: Resultsmentioning
confidence: 99%
“…Studies with the use of MMN in children with cleft lip and palate (27,38) and with recurrent otitis media (21) were found, showing the importance of such investigation with the use of an objective method, since otitis media and conductive hearing loss are pathologies that frequently occur in this population, leading to an indicator of risk for changes in auditory processing, language, speech and learning (49) . Studies involving other characteristics such as autistic spectrum disorder (21,34) , ADHD (19) , depression (35) , social isolation (37) , aphasia (39) and stuttering (31) found in this review, evidenced the variety of applications with the use of MMN in children, not only in auditory issues and auditory processing, and this procedure is therefore capable of promoting greater knowledge and diagnostic accuracy in several areas of clinical practice. By evaluating the PEDro scale (18) , it was observed that few articles met the checklist criteria, mainly regarding items of internal validity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations